Struggle Against Tyranical Regime In Tolstoy's Hadji Murad (1904): Marxist Criticism - FAUZI, ARIFAH NURUL (2016)
The major problem of this study is describing the struggle to fight against tyrannical regime in Chechnya reflected in Leo Tolstoy's Hadji Murad. The objective of this study is to analyze the structural elements of the novel, by finding character and characterization, setting, point of view, plot, and theme based on Marxist approach. The Writer employs qualitative method. The object of the study is Leo Tolstoy's novel Hadji Murad published in 1904. The writer uses two data sources: primary and secondary. The primary data source is the text of Hadji Murad by Leo Tolstoy, published by Pensylvania State University and the secondary data source are references and materials related to the study which are taken from books or internet. The technique of data collection is documentation and the technique of data analysis is descriptive analysis. Based on the analysis, the writer gets two conclusions. First, through Hadji Murad novel, Tolstoy delivers a message that hero is a matter of perspective. Second, the Hadji Murad novel reflects the social realities of the Chechen Muslims in the struggling against the Russian tyrannical regime that reflect Tolstoy's party to the proletariat class.